Integrated delivery of family planning and childhood immunisation services: A causal loop analysis of service responsiveness in Malawi - Jessie K. Hamon; Misozi Kambanje; Shannon Pryor; Alice S. Kaponda; Erick Mwale; Jayne Webster; Helen E.D. Burchett; Susannah H. Mayhew (SSM: Qualitative Research in Health, 2022)
Evidence suggests that integrating family planning (FP) services with childhood immunisations can increase postpartum contraceptive use by providing timely contact with FP services during the year following childbirth. However, little is known about clients' experiences of FP services within this context. Systems thinking was applied to examine the responsiveness of FP services that were integrated with childhood immunisations in routine outreach clinics across two districts of Malawi. A causal loop analysis of qualitative data captured through 1) structured exit interviews with clients (n=146) and 2) semi-structured interviews with clients (n=23) and their FP providers (n=10) was carried out to explain the system dynamics influencing the responsiveness of integrated FP services. Through this analysis, six feedback loops were identified as having a balancing effect on service responsiveness. Importantly, the clinic's client load was found to drive the responsiveness experienced by clients in the studied context. Overall, the results suggest that efforts to enhance the responsiveness of integrated FP services in outreach clinics should focus on 1) enhancing the providers' ability to alter the client flow in response to fluctuations in the clinic's client load, and 2) ensuring that an appropriate buffer of FP supplies is available in clinics to enable clients to consistently receive their preferred contraceptive irrespective of surges in demand. This study represents the first attempt at modelling the responsiveness of integrated FP services and its findings can be used to inform the design and delivery of FP services that are integrated with childhood immunisations in different settings.